The finances of the Southern Common Market (MERCOSUR) - Mariano, Karina Lilia Pasquariello [UNESP]; Ribeiro, Clarissa Correa Neto [UNESP] (My University, 2019)
Regional institutions in Latin America have as major characteristics a low degree of bureaucratisation and an intergovernmental logic. These are important elements to explain characteristics related to their financing aspects, as the integration budget is an indicator of a regional organisation’s vitality. This chapter analyses the Common Market of the South (MERCOSUR) and its budgetary process, based on an understanding of its institutional structure and asymmetries. The impact of the relaunching of MERCOSUR in the 2000s on the finances of the integration process is examined using the Fund for the Structural Convergence of MERCOSUR (FOCEM) as a detailed case. The choice to analyse FOCEM is justified due to its role in structural development, as it represents one of the main initiatives in the budgetary sphere. Finally, the present state of MERCOSUR is discussed, as well as the effects of the current crisis in Argentina and Brazil on the bloc’s finances and some conclusions are drawn regarding the budgetary future of this integration process and the limitations imposed by the intergovernmental structure.